Parental Practices Through Spiritual Aspects of Adolescents in Families in Malaysia and Indonesia - Zur Raffar, Izzah Nur Aida; Akbar, Muhammad Rizal; Nurmatias, Windayani; Nik Dahalan, Nang Naemah (Millah: Journal of Religious Studies, 2025)
The issue of parenting style in the family is one of the issues that need to be strengthened and given focus nowadays in order to overcome the increasing problems and cases of teenagers such as pregnancy outside of marriage, free sex, dumping babies, skipping school, smoking, drugs, rape, prostitution, robbery, theft, bullying, running away from home and murder. This is because one of the factors that contribute to the misbehavior of teenage children is caused by the behavior of parents and family values that are fading and fragile. A few teenagers were found to receive less love, attention, feeling alone, less appreciated and less trusted by their parents. Therefore, this study was conducted to identify the practice of parenting through the spiritual aspects of the family according to the perspective of teenagers. The design of this study is a quantitative survey study through the distribution of questionnaires to 523 respondents among teenagers in Malaysia and Indonesia. The data were analyzed descriptively using SPSS. Expectations of the results of this study can provide input on the parenting style practiced in the family. It can also be used by stakeholders in efforts to promote education and parenting guidance based on the guidance of al-Quran, al-Sunnah and the recommendations of Islamic scholars towards forming quality youth human capital as well as a prosperous family and society.